Managerialist ideology and the subjectivy of workers in the third sector (Revista de Administração, 2013)
This article deals with the impact of managerialist restructuring processes upon the subjectivity of workers in environmentalist third sector organizations, historically connected to philanthropy and the struggle for human rights. The growth of this organizational population has generated competition for resources, with a consequent search for managerial systems and models capable of enabling survival of each organization via comparative advantage associated with efficacy, efficiency, effectiveness and brand position. In this context, there is a perceptible adoption of models imported from the second sector - private and private interest oriented. Elements peculiar to managerialism, such as work intensification and acceleration, precarization of labor relations and the primacy of economic determinism, are also assimilated in the process. There is an investment in the cult of excellence and mobilization of the subject's psyche as a means of framing the person as a strategic organizational asset. Resulting practices clash with humanist values generally nurtured in the third sector, causing conflicts of rationalities and intrapsychic turmoil. A qualitative and exploratory research, based on interviews with professionals from four relevant environmental organizations in Brazil, has been developed in order to reveal, by means of discourse analysis, how subjects perceive the given phenomenon. Results show that the managerialist ideology has been assimilated by workers, that labor relations undergo precarization in favor of financial rentability of the organizational investments, that defense and adhesion strategies cause subjective suffering and that the third sector is dissociating itself from its historical identity of a sphere of agency marked by a substantive rationality.